Stability of Impulsive Differential Systems. (9th December 2013) - Reinfelds, Andrejs; Sermone, Lelde
Abstract : The asymptotic phase property and reduction principle for stability of a trivial solution is generalized to the case of the noninvertible impulsive differential equations in Banach spaces whose linear parts split into two parts and satisfy the condition of separation.